Arah Kebijakan Hukum Tentang Pengelolaan Sampah Di Kota Padang - Aprilla Laura Utari; Rahma Yulia; Atmarivaldi Rosel; Edo Nugraha; Elwidarifa Marwenny (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Waste is a big problem that needs more attention. According to the Ministry of Environment and Forestry, the total amount of waste in Indonesia is 187.2 million tons per year. Padang City as the capital of West Sumatra province also produces large amounts of waste. The accumulation of waste in Padang City in 2021 is around 233,385.96 tons per year. Padang City produces a total of 643.76 tons of waste per day in 2022. Most of this waste, around 62.80% is food waste. Apart from that, waste components such as glass (2.40%), plastic (12.40%), leaves/wood (6.84%), metal (0.19%), paper (5.70%), rubber (1 .50%), textiles (3.30%), and other waste (4.87%) related regulations regarding waste management in Padang City, namely PERDA Number 21 of 2012. However, in reality the waste problem never ends, in fact waste production continues to increase. The problem formulation is: 1) legal regulations related to waste management in Padang City; and 2) legal policies regarding waste management in Padang City. To answer this problem, a normative juridical type of research is used. So it can be concluded that 1) legal regulations related to waste management in Padang City, namely Padang City Regional Regulation Number 21 of 2012 which regulates waste management, West Sumatra Province Regional Regulation Number 8 of 2018 regulates Regional Waste Management, Republic of Indonesia Government Regulation Number 27 of 2020 concerning Specific Waste Management 2) the direction of legal policy regarding waste management in Padang City is by improving waste transportation services such as making transportation more efficient from residential areas to waste disposal sites because one of the problems related is the efficiency of waste logistics. This is believed to be due to the TPS function not being optimal at one location in the area, so it also has an impact on the current traffic system.